Developing Creative Thinking and Physics Students’ Achievement by using CPS - Pratiwi Pujilestari Alam; Ilham Assidiq; Elihami Elihami (Universitas Muhammadiyah Enrekang, 2020)
The purpose of this study is to explain the implementation of physical learning using the Creative Problem Solving (CPS) method to enhance creative thinking skills and learning outcomes in the X-IA2 SMA Negeri 1 Sidenreng Rappang class. The research approach used was Classroom Action Research across two learning stages, each of which consisted of planning, execution, observation and reflective phases. The results showed that studying physics with the CPS approach could boost students ' creative thinking. This is demonstrated by: (1) an improvement in the number of students who completed 12 during Cycle I to 26 in Cycle II with an average learning outcome of 77. N-gain in Cycle I of 0.20 is included in the low category and N-gain in the second cycle, 0.30 has been included in the medium category, (2) the average student learning group participation in the learning phase has been included in the Activity category, which has increased to the High Activity category, and (3) the use of innovative students.